2021
DOI: 10.1101/2021.01.19.427275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance of linkage disequilibrium and epistasis on the genetic variances and covariance between relatives in non-inbred and inbred populations

Abstract: Because no feasible theoretical model can depict the complexity of phenotype development from a genotype, the joint significance of linkage disequilibrium (LD), epistasis, and inbreeding on the genetic variances remains unclear. The objective of this investigation was to assess the impact of LD and epistasis on the genetic variances and covariances between relatives in non-inbred and inbred populations using simulated data. We provided the theoretical background and simulated grain yield assuming 400 genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Approaches that detect the magnitude of epistatic effects are not common. Viana and Franco-Garcia (2021) estimated the proportion between epistatic and genotypic variance and stated that the relationship is proportional to the percentage of epistatic genes. The authors also found estimates of epistatic variance due to duplicative genes of high magnitude (10 to 64%) in different generations of random mating and self-fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches that detect the magnitude of epistatic effects are not common. Viana and Franco-Garcia (2021) estimated the proportion between epistatic and genotypic variance and stated that the relationship is proportional to the percentage of epistatic genes. The authors also found estimates of epistatic variance due to duplicative genes of high magnitude (10 to 64%) in different generations of random mating and self-fertilization.…”
Section: Resultsmentioning
confidence: 99%